2021
DOI: 10.1002/pon.5783
|View full text |Cite
|
Sign up to set email alerts
|

Changes in depressive symptoms among family caregivers of patients with cancer after bereavement and their association with resilience: A prospective cohort study

Abstract: Objectives: To elucidate changes in depressive symptoms after bereavement and the impact of pre-loss resilience on such changes and on the extent of complicated grief and posttraumatic growth. Methods: Prospective cohort surveys were provided to family caregivers of patients with cancer in four palliative care units (PCUs) before and after bereavement. Preloss Connor-Davidson Resilience Scale scores, pre-and post-loss Patient Health Questionnaire-9 scores, post-loss Brief Grief Questionnaire scores, and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Three studies reported correlates of PTG among adolescents who lost a parent [37,38] or grandparent [39]. Eight studies reported the correlates of PTG in bereaved family caregivers of cancer patients [40][41][42][43][44][45][46][47] with one study specifically looking at bereaved parents [48]. All 12 studies used convenient sampling.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies reported correlates of PTG among adolescents who lost a parent [37,38] or grandparent [39]. Eight studies reported the correlates of PTG in bereaved family caregivers of cancer patients [40][41][42][43][44][45][46][47] with one study specifically looking at bereaved parents [48]. All 12 studies used convenient sampling.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All 12 studies used convenient sampling. Out of the 12 included studies, two were cohort studies [44,45] and the remaining were cross-sectional studies. All the study samples included a higher number of female participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The above two priorities are applied to the DeblurGAN depth model in the form of an additional loss function to see the in uence of the neural network on the deblurring performance. Experiments show that the discriminant pre-loss function can effectively improve the anti-disturbance performance of the depth model, and the mutual dual-channel energy loss function is more prominent [13]. The literature introduces the problem of Deblur GAN generation model, and redesigns an effective Deblur network architecture based on its own coding model.…”
Section: Related Workmentioning
confidence: 99%